2004
DOI: 10.1111/j.1439-0442.2004.00626.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Lactational Incidence of Displaced Abomasum and Milk Production Traits in German Holstein Cows

Abstract: The objective of this study was to analyse the heritabilitiy of the lactational incidence of displaced abomasum (DA) and the relationships of DA with milk production traits in German Holstein cows. Data were recorded between February 1999 and January 2000 in cooperation with five veterinary practitioners. Their veterinary practices were located in the northern part of Lower Saxony. The investigation included 160 dairy farms under the official milk-recording scheme with 9,315 cows. The lactational incidence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 15 publications
(49 reference statements)
1
25
0
Order By: Relevance
“…This is higher than other estimates from linear models reported by Lyons et al (1991), Appuhamy et al (2009), and Koeck et al (2013). Moreover, Wolf et al (2001) and Hamann et al (2004) with the use of threshold models reported heritability estimates above 0.50. The moderate to high heritability estimates of the present study can be attributed to a more accurate recording of the displacement made by the veterinarian and to the binary nature of the trait that posed no ambiguity of the severity of the disease and thus of the certainty of the diagnosis.…”
Section: Discussionmentioning
confidence: 65%
“…This is higher than other estimates from linear models reported by Lyons et al (1991), Appuhamy et al (2009), and Koeck et al (2013). Moreover, Wolf et al (2001) and Hamann et al (2004) with the use of threshold models reported heritability estimates above 0.50. The moderate to high heritability estimates of the present study can be attributed to a more accurate recording of the displacement made by the veterinarian and to the binary nature of the trait that posed no ambiguity of the severity of the disease and thus of the certainty of the diagnosis.…”
Section: Discussionmentioning
confidence: 65%
“…The main factors reported to precede LDA are a disturbed motility of the abomasum and an insufficient transport of gas (Van Winden and Kuiper, 2003). In GH, the prevalence for LDA was estimated at 1.2 to 2.6% (Wolf et al, 2001;Hamann et al, 2004) and can reach up to 7.5% in single herds (Poike and Fürll, 2000). The genetic component has a large effect on the incidence of LDA, as heritabilities have been estimated between 0.2 and 0.5 (Wolf et al, 2001;Hamann et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In GH, the prevalence for LDA was estimated at 1.2 to 2.6% (Wolf et al, 2001;Hamann et al, 2004) and can reach up to 7.5% in single herds (Poike and Fürll, 2000). The genetic component has a large effect on the incidence of LDA, as heritabilities have been estimated between 0.2 and 0.5 (Wolf et al, 2001;Hamann et al, 2004). Genome-wide association studies (GWAS) provide a step toward the identification of the underlying candidate genes for LDA and may open possibilities for selection against this disease.…”
Section: Introductionmentioning
confidence: 99%
“…However, the heritability of LDA reported in various studies ranged between 20% and 50% [1], [2] and thus is much higher than in any other common cattle disease.…”
Section: Introductionmentioning
confidence: 99%